1969
DOI: 10.1071/ch9691399
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonium salts. II. The reaction of bis-phosphonium salts with metal hydrides

Abstract: Ethane-1,2-bis-phosphonium salts are cleaved by sodium hydride to phos- phines in 55-80% yields with loss of the two-carbon bridge. The reaction is independent of the substituents at the phosphorus atoms. The same reaction is observed with an ethene-1,2-bis-salt and with but- 2-ene-1,4-bis(triphenylphosphonium) dibromide. It is suggested that a phosphorane is formed which subsequently fragments in a manner analogous to alkaline hydrolysis. ��� Lithium aluminium .hydride behaves similarly but loss of the bridge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Gallagher reported that ethylene and vinylene-bridged bis(phosphonium) salts treated with sodium hydride once again exhibited a concerted decomposition of both phosphonium centers to yield two phosphines, a proton and ethylene or acetylene gas. 136 The mechanism most likely proceeds according to that shown in Fig. 30, which is analogous to that observed for the alkaline hydrolysis of similar salts.…”
Section: Organometallic Hydride and Alkoxide Basesmentioning
confidence: 57%
See 2 more Smart Citations
“…Gallagher reported that ethylene and vinylene-bridged bis(phosphonium) salts treated with sodium hydride once again exhibited a concerted decomposition of both phosphonium centers to yield two phosphines, a proton and ethylene or acetylene gas. 136 The mechanism most likely proceeds according to that shown in Fig. 30, which is analogous to that observed for the alkaline hydrolysis of similar salts.…”
Section: Organometallic Hydride and Alkoxide Basesmentioning
confidence: 57%
“…30). 136 As observed for alkaline hydrolysis of phosphonium salts, benzyl and phenyl groups leave preferentially over alkyl groups, reflecting the order of anionic stability. 137,138 Conversely, Gough and Trippett noted an exception to this rule, as isopropyltriphenylphosphonium iodide yielded triphenylphosphine after treatment with LiAlH 4 .…”
Section: Organometallic Hydride and Alkoxide Basesmentioning
confidence: 95%
See 1 more Smart Citation
“…For the cleavage step, the bis‐phosphonium salt was introduced into a suspension of LiAlH 4 in anhydrous tetrahydrofuran (THF) and this mixture was refluxed for 24 h. The use of LiAlH 4 resulted in a reductive cleavage accompanied by the loss of ethylene and H 2 . The mechanism of the cleavage is described in Scheme by analogy with the mechanism proposed for DPPE 10. After the cleavage, a treatment was necessary to eliminate the excess of LiAlH 4 and to recover the water‐soluble phosphane.…”
Section: Resultsmentioning
confidence: 99%
“…The desired water‐soluble phosphanes can be obtained by alkylation then cleavage of DPPETS. This strategy uses the capacity of the quaternary bis‐phosphonium salts of 1,2‐bis(diphenylphosphanyl)ethane (DPPE) to be cleaved by lithium aluminium hydride (LiAlH 4 ) producing an alkyldiphenylphosphane with loss of the carbon bridge between the two phosphorus atoms 10. We report here the synthesis of five new disulfonated alkyldiphenylphosphanes ( 1–5 ; Scheme ) by using this new methodology.…”
Section: Introductionmentioning
confidence: 99%